The Screening and Correlation of Trace Elements in the Blood and Urine of School-Aged Children (5–12 Years): A Pilot Biomonitoring Study - Arlette A. Camacho-delaCruz; Oliver Mendoza-Cano; Xóchitl Trujillo; Miguel Huerta; Mónica Ríos-Silva; Irma Elizabeth Gonzalez-Curiel; Agustin Lugo-Radillo; María Fernanda Romo-García; Herguin Benjamin Cuevas-Arellano; Ángel Gabriel Hilerio-López; Ramón Solano-Barajas; Jaime Alberto Bricio-Barrios; et al. (Toxics, 2025)
Children constitute a population at risk from environmental exposure to trace elements. This study aimed to evaluate correlations between urinary and blood levels of multiple elements in school-aged children (5–12 years), assessing whether urine, a less invasive matrix, could complement or replace blood sampling. A pilot biomonitoring study was conducted, and 91 children provided urine and venous blood samples in which the levels of 17 contaminants (Al, As, Ba, Cs, Co, Cu, I, Pb, Li, Mn, Mo, Ni, Se, Sr, Te, Ti, and Zn) were assessed. Spearman correlation coefficients (rho) and 95% confidence intervals (CI) were computed. Urinary and blood levels of arsenic (rho = 0.23, 95% CI 0.01–0.44), lead (rho = 0.43, 95% CI 0.24–0.61), and strontium (rho = 0.22, 95% CI 0.03–0.40) showed significant correlations. These findings suggest that urine sampling could serve as a practical alternative to blood collection for monitoring specific trace elements like lead in pediatric populations, particularly in large-scale studies where participant compliance is critical. However, modest correlations for other elements highlight the need for element-specific validation before adopting urine as a universal biomonitoring matrix. Future research should explore the pharmacokinetic and exposure-related factors driving these relationships to optimize non-invasive surveillance strategies for children’s environmental health.